An Efficient Callus Induction and Plant Regeneration of Solanum nigrum (L.) - An Important Antiulcer Medicinal Plant - C. V. Naidu2*, T. M. Sridhar1 and (Journal of Phytology, 2011)
An efficient protocol devised for rapid callus induction and plantlet regeneration from young leaves, internodal explants of Solanum nigrum was described. For in vitro callus induction auxins such as 2, 4-D, IAA and NAA in combination with cytokinin BAP were used. High frequency of green compact callus was obtained in leaf explants cultured on MS medium supplemented with 3.0 mg/l NAA+0.5 mg/l BAP. The present study also describes successful plant regeneration from in vitro derived callus of young leaves. BAP or Kn alone or in combination with NAA and IAA was used for regeneration of plantlets from callus culture. High frequency and maximum number of multiple shoots were induced on MS medium supplemented with 3.0 mg/l BAP + 0.5 mg/l NAA. All the in vitro raised shoots with a length of 3-5 cm were transferred to rooting medium supplemented with different concentrations of IBA (0.25 – 1.0 mg/l). The best rooting response was observed on 0.5mg/l IBA. The well rooted plantlets were transferred to polybags containing soil + vermiculite in 1: 1 ratio for hardening. Finally the hardened plantlets were transferred to field conditions for maximum survivability.